Research progress of placental vascular pathophysiological changes in pregnancy-induced hypertension and gestational diabetes mellitus - Lei, Jiahui; Zhao, Meng; Li, Lingjun; Ji, Bingyu; Xu, Ting; Sun, Miao; Chen, Jie; Qiu, Junlan; Gao, Qinqin (Frontiers in Physiology, 2022)
The placenta is a vital organ for fetal development, providing the fetus with nutrients, oxygen, and other important factors. Placenta is rich in blood vessels. Abnormal placental vascular function and blood circulation may lead to insufficient blood supply to the fetus in the uterus, leading to serious consequences such as pregnancy complications, fetal distress and even stillbirth. Pregnancy-induced hypertension (PIH) and gestational diabetes mellitus (GDM) are common complications of pregnancy. Recent studies report that pregnancy complications are often accompanied by changes in placental vascular structure and function. What are the physiological characteristics of human placental blood vessels? What are the pathological changes in the state of PIH and GDM? What are the relationships between these pathological changes and the occurrence of these pregnancy complications? Answers to these questions not only increase the understanding of placental vascular characteristics, but also provide important information for revealing the pathological mechanism of PIH and GDM. This article will summarize the research on the pathological changes of placental blood vessels in PIH and GDM, hoping to further unravel the physiological and pathological characteristics of placental blood vessels in the state of PIH and GDM, provide information for guiding clinical treatment for PIH and GDM.